The Bahraini food based dietary guidelines: a holistic perspective to health and wellbeing - Farah Naja; Farah Naja; Sharfa Khaleel; Maryam Ebrahim Alhajeri; Buthaina Yusuf Ajlan; Najat Mohamed Abulfateh; Amna Ghassan Alawadhi; Marwa Husain Jan Bowah; Ayoub Al-Jawaldeh (Frontiers Media S.A., 2023)
The impact of food consumption extends well beyond the physical aspect of health to affect the mind, the society, and the environment. The biopsycho-ecological (BSE) theory recognizes the interplay between these factors and emphasizes the need for a holistic perspective to dietary recommendations. This manuscript presents a situation analysis of food consumption and diet-related diseases in Bahrain and describes the themes of the Bahraini Food based dietary guidelines (FBDG) and their alignment with the BSE constructs. Available data revealed low fruit and vegetable intake and excessive consumption of processed meat and sugary drinks in the country. These dietary habits are accompanied by a high burden of non-communicable diseases and their risk factors, anemia, and vitamin D deficiency. The Bahraini FBDG consisted of 11 context-specific themes and key messages that addressed the four dimensions of health depicted by the BSE theory, as follows: diet, physical activity, and food safety (body), physical activity, mindful eating and mental health (mind); family relations and cultural heritage (society), and food waste and environmental footprints of dietary intake (environment). The Bahraini FBDG present a model of dietary guidelines that adopted a holistic perspective to address health as they promote the role of food and dietary habits in maintaining the health of the body and that of the mind, the society, and the environment.